Extracorporeal Cardiopulmonary Resuscitation During Cesarean Delivery in a Patient With D-Transposition of the Great Vessels, Years Following Mustard Operation. Issue 4 (July 2021) - Brozzi, Nicolas Ariel; Cifuentes, Renzo Otoniel; Ghodsizad, Ali; Saab, Amanda; Yasin, Salih; Loebe, Mathias
Patients with surgically repaired complex congenital cardiac anomalies present unique characteristics that can make the implementation of extracorporeal membrane oxygenation (ECMO) support especially challenging. Very few series have reported the outcomes of ECMO support during pregnancy and peripartum. We report a case of successful extracorporeal cardiopulmonary resuscitation during cesarean delivery in a patient with surgically repairedd -transposition of the great arteries, and we discuss particular aspects that contributed to successful implementation of ECMO support and hospital discharge.